2012
DOI: 10.1111/j.1463-1326.2012.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

NPY modulates PYY function in the regulation of energy balance and glucose homeostasis

Abstract: Aims: Both the neuronal--derived neuropeptide Y (NPY) and the gut hormone peptide YY (PYY) have been implicated in the regulation of energy balance and glucose homeostasis. However, despite similar affinities for the same Y receptors, the co--ordinated actions of these two peptides in energy and glucose homeostasis remain largely unknown. Methods: To investigate the mechanisms and possible interactions between PYY with NPY in the regulation of these processes, we utilized NPY/PYY single and double mutant mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…13,16,24 Second, several of the novel endometrial carcinoma markers that we identified have been identified previously in other cancers (HS3ST2, 25 HTR1B, 26 MME 27 ) or involve important pathways in carcinogenesis such as Wnt signaling (ASCL2 28 ) and the Hedgehog pathway (ADCYAP1 29 ). In addition, NPY, one of our candidate markers, is proposed to function in energy balance and obesity, 30,31 which is notable because elevated body mass is strongly and consistently related to increased endometrial carcinoma risk. 32 Further studies are required to understand the role of these genes in endometrial carcinogenesis and to elucidate the etiologic heterogeneity of endometrial carcinomas reflected by the two groups of carcinomas with distinct methylation patterns observed in unsupervised hierarchical clustering.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,24 Second, several of the novel endometrial carcinoma markers that we identified have been identified previously in other cancers (HS3ST2, 25 HTR1B, 26 MME 27 ) or involve important pathways in carcinogenesis such as Wnt signaling (ASCL2 28 ) and the Hedgehog pathway (ADCYAP1 29 ). In addition, NPY, one of our candidate markers, is proposed to function in energy balance and obesity, 30,31 which is notable because elevated body mass is strongly and consistently related to increased endometrial carcinoma risk. 32 Further studies are required to understand the role of these genes in endometrial carcinogenesis and to elucidate the etiologic heterogeneity of endometrial carcinomas reflected by the two groups of carcinomas with distinct methylation patterns observed in unsupervised hierarchical clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Combined deletion of PYY and NPY retards, however, the recovery from the hypophagic effect of BCG. To the contrary, hyperphagia provoked by food deprivation is enhanced in PYY−/− animals but left unchanged in NPY−/− as well as NPY−/−;PYY−/− mice (Zhang et al ., ), although another study holds that fasting‐induced hyperphagia is also enhanced in NPY−/− animals (Erickson et al ., ). These observations suggest that the reduction of food intake caused by fasting, on the one hand, and BCG, on the other hand, involves the NPY/PYY system to a different extent.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide YY consists of two forms, PYYa and PYYb (previously called PY) (Wahlestedt and Reis, 1993; Cerdá-Reverter and Larhammar, 2000; Sundström et al, 2013) and is a brain-gut peptide that acts as an anorexigenic signal in mammals (Blevins et al, 2008; Karra et al, 2009; Zhang et al, 2012). Interestingly, one of the first studies showing an effect of PYY on feeding in mammals used fish PYY (Balasubramaniam et al, 1992).…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%